Game qualities of women basketball players (agility, reliability and efficiency) in league games - Basinac, I.; Mikic, B.; Bajgoric, B. (Acta Kinesiologica, 2009)
Agility, reliability and realization efficiency of the leading components of the competitive game of the analyzed women basketball players were evaluated by the analysis of 5 video-recorded games each of the six analyzed the First women's basketball league clubs in Bosnia and Herzegovina. The agility results, reliability and realization efficiency, sample by defined leading components were given individually and as a sum for a certain woman basketball player and each analyzed team. Dominant characteristic of the women basketball players classified by specific separated groups are related to: efficiency, reliability and agility jump shot for three points (SEFUU, SEFSUP AND SEFSUS), reliability in doing the free throw (SEFPENS), agility and block reliability and throwing the ball in the basket (doing the hoops) (SEFBLPP, SEFBLPS), and reliability of jump shot from different positions.